Synthesis of 1,9-Diazaphenoxazine Carboxamide Derivatives via Buchwald-Hartwig Amidation Protocol - Edoka, O.L.; Okoro, U.C.; Ugwu, D.I. (Asian Journal of Chemistry, 2015)
Tandem amidation catalyzed synthesis of linear diazaphenoxazine carboxamide derivatives (18a-e) is reported. This was achieved by the reaction of 2-amino-3-hydroxypyridine (11) and 2,3,5-trichloropyridine (12) in aqueous basic medium to afford 3-chloro-1,9-diazaphenoxazine (13) as white solid crystals. Compound 13 was then subjected to Buchwald-Hartwig amidation coupling reaction with various carboxamides (17a-e) in the presence of 1,4-bis(2-hydroxyl-3,5-di-tert-butyl benzyl)piperazine (16) as ligand, Pd(OAc)2 as palladium source catalyst, K2CO3 as base and 50:50 DMF and toluene as solvent at 110 ºC for 2 h to afford the linear diazaphenoxazine carboxamide derivatives (18a-e) in good to excellent yield. The water mediated pre-activation of the catalyst was monitored visually using colour change from yellow to black. The compounds were characterized using UV-visible, FTIR, 1H NMR, 13C NMR spectroscopy and elemental analysis.